Analyzing the effects of treating hypothyroidism and subclinical hypothyroidism on body mass - Diniz Silva, Ana Cristina (2016)
Hypothyroidism and subclinical hypothyroidism (SCH) are common endocrine dysfunctions, mostly affecting females. The prevalence of overt hypothyroidism is estimated in 2%, whereas SCH may affect as much as 3-15% of the population. Both conditions evolve with near similar symptoms and one of the commonest presentations is weight gain. The goal of the standard thyroid replacement therapy is to achieve euthyroidism, both clinically and biochemically, which is assessed by the circulating thyroid stimulating hormone (TSH) within the normal range of reference. Although patients tend to correlate their overweight/obesity with overt or subclinical hypothyroidism, it remains difficult to determine how much of the weight gain can be attributed to these conditions, as their onset is not always clear. In addition, despite highly expected, weight loss following hormonal replacement therapy cannot be assured, according to the current evidence. The aim of this article is to evaluate the relationship between TSH levels and weight, and the effects of treating hypothyroidism and SCH on body mass, specifically looking at weight loss, through a detailed review of the available literature.